Pneumocystis jirovecii pneumonia in AIDS and non-AIDS immunocompromised patients – an update - Lee, Yuan-Ti; Chuang, Ming-Lung (The Journal of Infection in Developing Countries, 2018)
Introduction: Pneumocystis jirovecii (PJ) pneumonia (PJP) is an important opportunistic infection affecting various types of immunocompromised patients and is associated with an increased risk of mortality. PJ is a unique fungal pathogen which is increasingly common and maybe associated with a higher mortality rate in patients without AIDS. We present the characteristics of PJP, diagnosis, and treatment outcomes between AIDS and non-AIDS patients. Methodology: We conducted a review of studies of AIDS and non-AIDS patients with PJP using PubMed to search for studies until December 2017. Results: The annual incidence of AIDS-PJP decreased from 13.4 to 3.3 per 1000 person-years in industrialized countries, while the incidence of non-AIDS-PJP varied widely. Both groups had similar clinical manifestations and radiological features, but the non-AIDS-PJP group potentially had a more fulminant course, more diffuse ground glass opacities, and fewer cystic lesions. The mortality rate decreased in the AIDS-PJP group after the advent of antiretroviral therapy; however, the mortality rate remained high in both groups. A laboratory diagnosis was usually nonspecific; CD4+ T-cell < 200 cells/mL or < 14% favored AIDS-PJP. Serum 1,3-β-D-glucan (BDG) had a high diagnostic odds ratio. Combining BDG and lactic dehydrogenase improved the diagnosis of AIDS-PJP. Histopathological staining and polymerase chain reactions could not discriminate infection from colonization when the result was positive. The use of antibiotics, prophylaxis, and adjunctive corticosteroids was controversial. Conclusions: Early diagnosis and treatment can be achieved through vigilance, thereby improving the survival rate for PJP in immunocompromised patients.